O canto dos excluídos! Interfaces entre a saúde e a justiça na reinserção de pessoas inimputáveis - Gomes, Luiz Guilherme Araújo (2020)
ABSTRACT: "The singing of the excluded!" brings the narratives of João-de-barro and Urutau, subjects considered inimputable from a psychiatric diagnosis, they done the Security Measure hospitalized in a treatment unit inserted in the Central Penitentiary of the state of Mato Grosso. The first has committed a parricide and the second a theft, in their narratives they expose the situations they experienced until culminating in this hospitalization, the last among the others that were submitted. They portray the absence of formal support from the State in the consolidation of public mental health policies, the interventions carried out by the justice in the repression of the crimes committed and the difficulties of access to education, quality work and others, which could be a protection for situations of violence and exclusion suffered. Inserted in this plot, the Weavers, professionals of a Team of Evaluation and Monitoring of Preventive Measures, are responsible for the process of reinsertion of hospitalized subjects. The Team unties the knots and redoes the plots mediating the relationships, people and institutions that present themselves to these subjects considered dangerous, a quality that is attributed throughout the legal-psychiatric process and is established for carrying out punishment / treatment interventions, but it produces a series of effects and leaves marks that make the reintegration process even more difficult. This dangerousness would be, therefore, the central element for the ordering of a series of institutions, groups and people in their surroundings, enabling their return to living in society under the maintenance of control and surveillance. In view of this problem, the objective of this work was to analyze the dangerousness as the originator of practices and knowledge in the care of non-imputable people in conflict with the law, in Mato Grosso. From a qualitative approach, of a comprehensive nature and based on the socio-anthropological perspective, the subjects were observed and interviewed during the contact with people and institutions destined to their care. The data produced were organized in order to understand the perspectives on the dangerousness and on these subjects in reinsertion and how their effects are evident. For the treatment and analysis of data, thematic analysis was chosen, resulting in three chapters: “Can the non-imputable speak? The narratives of João-de-Barro and Urutau”, showing the effects of the device in the lives of the subjects from their speech; “Sewing Networks: the Team for the Assessment and Monitoring of Preventive Measures in Health Care in Mato Grosso”, evoked by the Team about the unimputable subjects, the institutions involved and the shared tensions; and “Attention to the Mental Health of the unimputable subject”, which discussed the elements that are evoked in the reinsertion process. Important issue for Public Health, concerned with the life and illness processes to which people in intense psychosocial suffering are subjected. These subjects find in supervisory/control the possibility of supervised reintegration, under the weight of responsibility in the family, often without the proper support from the State. Making it necessary to create collectively constructed strategies, as long as they prioritize their co-participation and autonomy in the reintegration process.